Comparison between left atrial features in well-controlled hypertensive patients and normal subjects assessed by three-dimensional speckle tracking echocardiography - Onishi, Noriyuki; Kawasaki, Masanori; Tanaka, Ryuhei; Sato, Hidemaro; Saeki, Maki; Nagaya, Maki; Sato, Noriaki; Minatoguchi, Shingo; Watanabe, Takatomo; Ono, Koji; Arai, Masazumi; Noda, Toshiyuki; et al. (Journal of Cardiology, 2014)
Three-dimensional speckle tracking echocardiography (3D-STE) has a major advantage in the improvement of accuracy in the evaluation of cardiac chamber volume without any geometrical assumption. Thus, the aim of this study was to use 3D-STE to elucidate the features of left atrial (LA) volume and function that are altered by hypertension (HTN) by comparing well-controlled HTN patients with normal subjects. Conventional echocardiographic parameters and LA phasic volume and function were measured from apical view by 3D-STE in 40 patients with well-controlled HTN [systolic blood pressure (BP) <140 and diastolic BP <90mmHg for more than one year] and 40 normotensive subjects. The passive LA emptying function (EF) in the patients with well-controlled HTN significantly decreased (16±7% vs. 22±8%, p=0.0013) and the active LAEF in patients with well-controlled HTN significantly increased (35±10% vs. 30±9%, p=0.029) compared with the values in normotensive subjects. Multivariate logistic regression analysis revealed that E/e′ was an independent determinant of well-controlled HTN. The maximum LA volume index was correlated with elevated E/e′ (r=0.30, p=0.0064), whereas the maximum LA volume index was not correlated with LV mass index or systolic BP. This change was independent of age. These results suggest that LV diastolic dysfunction occurs before structural changes of left atrium and left ventricle even in patients with well-controlled HTN.